Strategy investments in zero-sum games - Garcia, Raul; Hosseinian, Seyedmohammadhossein; Pai, Mallesh; Schaefer, Andrew J. (Optimization letters, 2024)
We propose an extension of two-player zero-sum games, where one player may select available actions for themselves and the opponent, subject to a budget constraint. We present a mixed-integer linear programming (MILP) formulation for the problem, provide analytical results regarding its solution, and discuss applications in the security and advertising domains. Our computational experiments demonstrate that heuristic approaches, on average, yield suboptimal solutions with at least a 20% relative gap with those obtained by the MILP formulation.